2015
DOI: 10.1134/s0003683815030138
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of pendimethalin nitroreductase from Bacillus circulans

Abstract: A pendimethalin nitroreductase was purified from Bacillus circulans to 52 fold increase with a recovery of 21.1% and had a specific activity of 4.16 U/mg. The molecular weight was 27 kDa. The optimum pH and temperature were 7.5 and 35°C, respectively. Fe 2+ , Ca 2+ , Mg 2+ and Mn 2+ did not cause any effect on the enzyme activity, whereas Ag + , Hg 2+ significantly inhibited it. The pendimethalin nitroreductase from B. circulans required NADPH as cofactor. It was not affected by GSH, DTT, L Cys and β mercaptoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The enzymes reduced both nitro groups on trifluralin, oryzalin, and butyralin, but only reduced one nitro group on pendimethalin. A prior study 77 purified a similar nitroreductase enzyme from Bacillus circulans which was also active on several dinitroanilines, although in this case, the corresponding gene was not identified, so it is hard to know to what extent this enzyme was related in sequence to the B. subtilis Y3 enzyme. Reduction of the nitro-groups of trifluralin has also been reported for Pseudomonas f luorescens isolates; 78 this study also reported dealkylated metabolites, but unfortunately the metabolite identifications were tentative and the enzymes involved were not identified.…”
Section: Cultures Of Microbesmentioning
confidence: 98%
“…The enzymes reduced both nitro groups on trifluralin, oryzalin, and butyralin, but only reduced one nitro group on pendimethalin. A prior study 77 purified a similar nitroreductase enzyme from Bacillus circulans which was also active on several dinitroanilines, although in this case, the corresponding gene was not identified, so it is hard to know to what extent this enzyme was related in sequence to the B. subtilis Y3 enzyme. Reduction of the nitro-groups of trifluralin has also been reported for Pseudomonas f luorescens isolates; 78 this study also reported dealkylated metabolites, but unfortunately the metabolite identifications were tentative and the enzymes involved were not identified.…”
Section: Cultures Of Microbesmentioning
confidence: 98%
“…Nitroreductases (NTRs) are biological enzymes of the flavin enzyme family that reduce nitroaromatic compounds to the corresponding nitrite, hydroxylamine, or amino derivatives using nicotinamide adenine dinucleotide (NADH) or nicotinamide adenine dinucleotide phosphate (NADPH) as an electron donor. The hypoxic environment of the tumor tissue results in the overexpression of NTRs in tumor cells, highlighting the importance of NTR monitoring for clinical diagnosis and tumor therapy. , Compared with the role of NTRs in mammalian cells, bacterial NTRs are thought to play a vital role in the antibacterial activity of nitroimidazole antibiotics, such as chloramphenicol. In bacterial cells, intracellular reduction of the nitro groups of 5-nitroimidazole drugs (metronidazole, tinidazole, and ornidazole) can be mediated by endogenous NTRs along with the production of active radical intermediates, which inhibits bacterial colonization through the inhibition of DNA synthesis. Clinically, emerging problems of resistance to 5-nitroimidazole drugs make the treatment of bacterial infections a growing challenge .…”
mentioning
confidence: 99%